2008
DOI: 10.1002/cncr.23523
|View full text |Cite
|
Sign up to set email alerts
|

Histologic grade is correlated with outcome after resection of hepatic neuroendocrine neoplasms

Abstract: BACKGROUND.The behavior of neuroendocrine neoplasms is poorly defined, and predictors of outcome after surgical resection have yet to be identified. Consequently, guidelines for treatment remain unclear. Current pathologic classification systems do not permit meaningful discrimination of hepatic neuroendocrine neoplasms.METHODS.The authors reviewed prospectively maintained databases from 2 institutions of patients who underwent hepatic resection for neuroendocrine neoplasms between 1990 and 2006. Patient, tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 95 publications
(129 reference statements)
3
63
0
Order By: Relevance
“…Irrespective of the primary tumor site and in absence of nonresectable extrahepatic disease, surgery should therefore be proposed in all well-differentiated GEP-NEN patients with LM in whom complete resection is feasible. It should be noted that individuals with highgrade NENs probably represent a separate disease entity and are unsuitable for surgical treatment as they exhibit a median overall survival of only 6 months after partial hepatectomy (Cho et al 2008). It is therefore critical that a core needle biopsy or laparoscopically guided biopsy is undertaken before the decision for surgery to establish tumor grading.…”
Section: R170mentioning
confidence: 99%
“…Irrespective of the primary tumor site and in absence of nonresectable extrahepatic disease, surgery should therefore be proposed in all well-differentiated GEP-NEN patients with LM in whom complete resection is feasible. It should be noted that individuals with highgrade NENs probably represent a separate disease entity and are unsuitable for surgical treatment as they exhibit a median overall survival of only 6 months after partial hepatectomy (Cho et al 2008). It is therefore critical that a core needle biopsy or laparoscopically guided biopsy is undertaken before the decision for surgery to establish tumor grading.…”
Section: R170mentioning
confidence: 99%
“…Various groups have reported impressive 5-year survival rates up to 87% following surgical resection of NET liver metastases (Que et al 1995, Chamberlain et al 2000, Nave et al 2001, Musunuru et al 2006. Unfortunately recurrence is observed in the majority of patients (Cho et al 2008). For some patients, subtotal resection of the bulk of tumour may be appropriate for palliation of symptomatic recurrence from local effects or hormone secretion (Sarmiento et al 2003).…”
Section: Surgerymentioning
confidence: 99%
“…Several studies have demonstrated adverse movement in neuroendocrine tumors originating in the pancreas 3,17, . Patients with liver metastases from TNE have high recurrence rate 28,[30][31][32] and less than 15% are cured 6,13 . In this study, relapse occurred in 46.1% of patients who underwent complete resection of liver metastases.…”
Section: Results Results Results Resultsmentioning
confidence: 99%